2013
DOI: 10.1097/dcr.0b013e3182765c43
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Puncture or Laceration in Colorectal Surgery

Abstract: Accidental puncture or laceration is more likely to occur in complex colorectal operations. The clinical consequences range from none to significant depending on the specific type of injury. To make accidental puncture or laceration a more meaningful quality indicator, we advocate that groups who use the measure eliminate the injuries that have no bearing on surgical outcome and that risk adjustment for operative complexity is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A recent retrospective review of accidental punctures or lacerations during colorectal surgery revealed nine ureteral injuries in a series of 2897 colorectal operations. Interestingly, history of prior surgery was not associated with an increased incidence of extraintestinal organ injury [Kin et al 2013]. Vascular procedures may cause an intense inflammatory response around the ureters and result in either stricture or fistula as shown in Figure 1.…”
Section: General and Vascular Surgerymentioning
confidence: 99%
“…A recent retrospective review of accidental punctures or lacerations during colorectal surgery revealed nine ureteral injuries in a series of 2897 colorectal operations. Interestingly, history of prior surgery was not associated with an increased incidence of extraintestinal organ injury [Kin et al 2013]. Vascular procedures may cause an intense inflammatory response around the ureters and result in either stricture or fistula as shown in Figure 1.…”
Section: General and Vascular Surgerymentioning
confidence: 99%
“… Denotes the codes 9982 (Accidental puncture or laceration during a procedure, not elsewhere classified) and E8700 (Accidental cut, puncture, perforation or haemorrhage during surgical operation) . …”
Section: Resultsmentioning
confidence: 99%
“…In colorectal operations, serosal injuries or enterotomies are the most common accidental punctures or lacerations, and often occur in the course of adhesiolysis in reoperative surgery, but were found to be more a marker of surgical complexity than of surgical quality. 14,15 We may be able to use such markers to identify cases of greater complexity and, thus, perform risk adjustment to ultimately improve the accuracy of surgical quality metrics.…”
Section: Implications For Surgical Qualitymentioning
confidence: 99%